2016
DOI: 10.1371/journal.pone.0152767
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA-ROR Mediates the Reprogramming in Cardiac Hypertrophy

Abstract: BackgroundCardiac hypertrophy associated with various cardiovascular diseases results in heart failure and sudden death. A clear understanding of the mechanisms of hypertrophy will benefit the development of novel therapies. Long non-coding RNAs (lncRNAs) have been shown to play essential roles in many biological process, however, whether lncRNA-ROR plays functional roles in the reprogramming of cardiomyocyte remains unclear.Methodology/Principal FindingsHere we show that lncRNA-ROR plays important roles in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 26 publications
1
60
0
1
Order By: Relevance
“…Related miRNAs consist of miR-145, miR-205, miR-133 and miR-34 [31,32,34,36,38,48,49]. Among which, the miR-145 is the one who gains most attention in the field of linc-ROR.…”
Section: Linc-ror Functions As a Cerna To Regulate The Cell Progressesmentioning
confidence: 99%
See 1 more Smart Citation
“…Related miRNAs consist of miR-145, miR-205, miR-133 and miR-34 [31,32,34,36,38,48,49]. Among which, the miR-145 is the one who gains most attention in the field of linc-ROR.…”
Section: Linc-ror Functions As a Cerna To Regulate The Cell Progressesmentioning
confidence: 99%
“…The study provides evidences that linc-ROR prevented the degradation of miR-205 target genes, such as ZEB2, which is a EMT inducer. In addition, there are evidences that increased linc-ROR promotes the re-expression of fetal gene (ANP and BNP) and cardiomyocyte hypertrophy related genes via behaving as a ceRNA to inhibit the expression and function of miR-133 [49,63]. By suppressing miRNAs, linc-ROR may contribute to the regulation of genetic networks during development and tissue regeneration and may lead to new therapies for many diseases.…”
Section: Linc-ror Functions As a Cerna To Regulate The Cell Progressesmentioning
confidence: 99%
“…Cardiac hypertrophy is related to a wide range of pathological and physiological elements, and its growth is closely correlated with the expression of the embryonic genes including ANP and BNP and improved protein synthesis [9,24]. In addition, it has been reported that lncRNAs The silence of HOXA9 outstandingly decreased the improved hypertrophic responses including the cell surface area, the mRNA and protein levels of ANP and BNP.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the inhibition of CHAER expression could reduce cardiac hypertrophy and other types of heart dysfunctions. Moreover, another hypertrophic inducer is ROR (regulator of reprogramming) and functions as miR-133 sponge, since overexpression of miR-133 can reverse the pro-hypertrophic effect of ROR [81]. Conversely, a recent study discovered a class of anti-sense lncRNAs with cardio-protective effect, known as myosin heavy-chain associated RNA transcripts (MHRT or Myheart) [82].…”
Section: Lncrna-based Therapy For Cardiovascular Diseasesmentioning
confidence: 99%